BRAC University new campus development project construction schedule (01.01.2022-31.01.2022) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding BRAC University new campus development project construction schedule from 01.01.2022 to 31.01.2022.